Self-Related Health, Physical Activity and Complaints in Swedish High School Students - Marie Alricsson; Bodil J. Landstad; Ulla Romild; Suzanne Werner (The Scientific World Journal)
The aim of this investigation was to study self-related health, physical activity and level of exertion, as well as body complaints in Swedish high school students. A total of 993 high school students aged 16–19 years participated in the study. A questionnaire was completed at school and included questions about self-related health, physical activity behavior, type of physical activity/sport, intensity, duration, possible injuries or complaints, and absence from physical training at school, during the last 3 months. The results showed that 26% of the high school students participated in sports on a regular basis. Males reported significantly better health than females (p < 0.0005). A significantly higher number of females participated in physical activities at a lower level of effort (p < 0.0005) and a higher number of males trained at a higher level of effort (p < 0.005). Sixtyone percent reported body pain during the last 3 months, representing a higher number of females than males (p = 0.03). A higher number of females than males reported complaints from the back (p = 0.002), the knees (p = 0.015), the neck (p = 0.001), and the hip (p = 0.015). Females with body complaints reported poorer health than those without complaints. There was a correlation between poor self-related health and a lower level of physical effort (0.219; p < 0.001). The results showed that the prevalence of musculoskeletal symptoms was high in this population and demonstrated a certain association with self-related health. Therefore, it is important to make it easy for adolescents to perform physical activity at school and during their leisure time in order to prevent chronic diseases.